The Role of Cytosolic Lipid Droplets in Hepatitis C Virus Replication, Assembly, and Release. (14th April 2023) - Awadh, Abdullah A.
Abstract : The hepatitis C virus (HCV) causes chronic hepatitis by establishing a persistent infection. Patients with chronic hepatitis frequently develop hepatic cirrhosis, which can lead to liver cancer—the progressive liver damage results from the host's immune response to the unresolved infection. The HCV replication process, including the entry, replication, assembly, and release stages, while the virus circulates in the bloodstream, it is intricately linked to the host's lipid metabolism, including the dynamic of the cytosolic lipid droplets (cLDs). This review article depicts how this interaction regulates viral cell tropism and aids immune evasion by coining viral particle characteristics. cLDs are intracellular organelles that store most of the cytoplasmic components of neutral lipids and are assumed to play an increasingly important role in the pathophysiology of lipid metabolism and host-virus interactions. cLDs are involved in the replication of several clinically significant viruses, where viruses alter the lipidomic profiles of host cells to improve viral life cycles. cLDs are involved in almost every phase of the HCV life cycle. Indeed, pharmacological modulators of cholesterol synthesis and intracellular trafficking, lipoprotein maturation, and lipid signaling molecules inhibit the assembly of HCV virions. Likewise, small-molecule inhibitors of cLD-regulating proteins inhibit HCV replication. Thus, addressing the molecular architecture of HCV replication will aid in elucidating its pathogenesis and devising preventive interventions that impede persistent infection and prevent disease progression. This is possible via repurposing the available therapeutic agents that alter cLDs metabolism. This review highlights the role of cLD in HCV replication.